Produtividade, composição bromatológica e parâmetros fermentativos da silagem de canola (Brassica napus L.) submetida a testes de polinização - Ströher, Sandra Mara (2018)
The work was carried out with the objective of evaluating the production, fermented profile and nutritional production of canola silage (Brassica napus) submitted to different pollination testes. The experiments lasted from 06/17/2016 to 04/02/2017 and; from 06/17/2016 to 10/14/2016 and 05/17/2017 to 03/10/2017. In the first and second experiments, the blocks consisted of a combination of three pollinator tests, with a pollinated cage area with a colony of apis mellifera, a covered area with a pollinating cage without bees and a free demarcated area to visit control, with four replicates and five opening times (0, 30, 60, 90 and 120 days), totaling 60 experimental units. The objectives were to evaluate the bromatological and; Microbial fermentative and microbiological parameters of canola silage (B. napus) submitted to pollination tests. The experimental design was a randomized complete block design with no subdivided plots. In the experiment, we verified the effect of years and interactions between the years and the other factors studied. In dry matter, mineral and organic matter, crude protein, ethereal extract, acid detergent fiber and neutral detergent, nitrogen insoluble in acid detergent and neutral detergent, lignin, cellulose, hemicellulose, hydrogenation potential , temperature, humidity, water activity, fermentative capacity, soluble carbohydrates, ammoniacal nitrogen, breakdown of aerobic stability, loss of gases and effluents, total loss of dry matter, dry matter recovery, buffer capacity, electrical conductivity, mass acid bacteria enterobacteria and clostridium. The number of grains per plant weight, number of grains per weight, weight of one thousand grains, number of grains per weight and weight, plant weight, silica size, plant germination weight, grain extract content and production per hectare. The pollination testis interfered in the contents of ethereal extract, acid insoluble nitrogen, lignin, fracture resistance and breakage of aerobic stability and the canola has fermentative characteristics for the feeding process, nutritious and nutritious nutrition of ruminants. The presence of pollinating agents in sugarcane increased by 35.53% in the number of silica plants per plant; 17.58% in the number of grains per silica and 41.19% in the production of seeds per hectare.